2020
DOI: 10.3389/fpsyt.2020.00246
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Another Person Influences Oscillatory Cortical Dynamics During Dual Brain EEG Recording

Abstract: Humans are innately social creatures and the social environment strongly influences brain development. As such, the human brain is primed for and sensitive to social information even in the absence of explicit task or instruction. In this study, we examined the influence of different levels of interpersonal proximity on resting state brain activity and its association with social cognition. We measured EEG in pairs of 13 typically developing (TD) adults seated in separate rooms, in the same room back-to-back, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Finally, we observed stronger inter-brain synchrony in the beta band in the FtF condition than in the FtFO or BtB condition, and stronger inter-brain synchrony in the beta band in the FtFO condition than in the BtB condition. These results advance the existing hyperscanning literature by demonstrating that both dyadic visibility and spatial orientation affect the strength of inter-brain synchrony during social interaction (see Dai et al., 2018 ; Jiang et al., 2012 ; Rolison et al., 2020 ; Vestner et al., 2019 ; Yun, 2013 ). Recent work has suggested that increases in beta-band imaginary coherence between interlocutors reflects the establishment of shared perceptuomotor and cognitive representations during human interaction ( Dikker et al., 2021 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Finally, we observed stronger inter-brain synchrony in the beta band in the FtF condition than in the FtFO or BtB condition, and stronger inter-brain synchrony in the beta band in the FtFO condition than in the BtB condition. These results advance the existing hyperscanning literature by demonstrating that both dyadic visibility and spatial orientation affect the strength of inter-brain synchrony during social interaction (see Dai et al., 2018 ; Jiang et al., 2012 ; Rolison et al., 2020 ; Vestner et al., 2019 ; Yun, 2013 ). Recent work has suggested that increases in beta-band imaginary coherence between interlocutors reflects the establishment of shared perceptuomotor and cognitive representations during human interaction ( Dikker et al., 2021 ).…”
Section: Discussionsupporting
confidence: 82%
“…To this end, we asked participants to converse in a face-to-face spatial orientation (multimodally, i.e., with mutual, visual access), a face-to-face spatial orientation with a visual occlusion (vocal only), and in a back-to-back spatial orientation (vocal only). This manipulation ensured that we could capture any effects on intra- and inter-brain neural activity caused by spatial orientation as well as effects caused by dyadic visibility, a fundamental distinction that has so far been missing from the literature (see e.g., Jiang et al., 2012 ; Rolison et al., 2020 ; Yun, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the neurobiological basis of social behaviors cannot be explored in a social vacuum as the brain responds differently to virtual vs. actual stimuli: i.e. their perception in different contexts can elicit distinct types of brain activity (Rolison et al ., 2020 ). Understanding the functioning of the social brain requires a comprehensive investigation of the neural features of at least two or multiple individuals during interactions (Kingsbury et al ., 2019 ); this so-called “second-person neuroscience” (Schilbach et al ., 2013 ) or “interpersonal neuroscience” (Pan et al ., 2022b ) is a promising trend in psychiatry (Schilbach, 2016 ; Pan & Cheng, 2020 ; Dumas, 2022 ).…”
Section: Recent Methodological Developments In Psychiatry and Interpe...mentioning
confidence: 99%
“…Additionally, small variations between experimental conditions and analyses could influence the outcome. For example, the presence of another person in the experimental room, even without an explicit task, diminishes oscillatory behavior (Rolison et al., 2020). Additionally, the effect of movements—which is especially a problem in research with infants—may introduce artifacts in the EEG data (e.g., see Georgieva et al., 2020; Köster, 2016; Tal & Yuval‐Greenberg, 2018), and may thereby influence power, phase estimations, and intra‐ and interpersonal correlations.…”
Section: Dual‐eeg Analysis Techniquesmentioning
confidence: 99%